Capital Breeding in a Diapausing Copepod: A Transcriptomics Analysis - Roncalli, Vittoria; Cieslak, Matthew C.; Hopcroft, Russell R.; Lenz, Petra H. (Frontiers in Marine Science, 2020)
Capital breeders must balance the energetic requirements of cellular function and the cost of reproduction in organisms. The subarctic copepod Neocalanus flemingeri, a small planktonic crustacean, depends on a short annual phytoplankton bloom to acquire the energy needed to support a non-feeding female adult that enters a period of diapause prior to spawning five to seven months later. After emergence from diapause, the reproductive program takes two-months starting with germline development. The relationships between energy utilization, cellular maintenance and oogenesis were investigated through gene expression profiling. The sequential up- and down-regulation of genes involved in cellular maintenance and metabolic pathways coincided with four developmental groups: diapause, emergence from diapause and early oogenesis, mid to late oogenesis, and finally spawning and end-of-life. Up-regulation of genes involved in cellular homeostasis, glycolysis and lipid catabolism as well as germline development characterized the transition from diapause to post-diapause. The down-regulation of genes involved in cellular homeostasis coincided with the up-regulation of genes related to mid-late oogenesis and protein degradation. As females started to spawn, genes involved in protein ubiquitination and programmed cell death became up-regulated. Energy allocation and utilization is highly dynamic in N. flemingeri during the non-feeding period and it is linked to the provisioning and maturation of eggs through lipid catabolism and autophagy. The data suggest the presence of a mechanism that regulates fecundity to match the availability of stored resources. Such a mechanism would minimize reproductive failure when resources and contribute to the resilience of the species.